Benefits of building information modeling (BIM) for construction projects success in Pakistan - Khan, Maira; Warraich, Imran Asghar; Sarwar, Nadeem; Yaman, Orhan (Nature Portfolio, 2026)
Adoption of building information modeling (BIM) by the construction industry signifies a paradigm shift in its project management and design approaches. This study uses a serial mediation model to explain the relationship between BIM benefits and project success (PS), focusing on the crucial aspects of BIM implementation (BIMI), internal stakeholder satisfaction (ISS), and top management support (TMS). A survey was conducted, and a structural equation modelling approach (SEM) was used to validate the constructs. A total of 314 valid responses were collected from Pakistan Engineering Council (PEC) registered firms to test the proposed hypotheses. The results indicate that BIMI mediates the relation between BIMB and PS. Also, ISS mediates the relation between BIMB and PS. Furthermore, BIMI and ISS sequentially mediate the relationship between BIMB and PS. However, the moderation of TMS was not established between BIMB and BIMI. Findings show that the influence of BIM benefits on project success follows a sequential mediation pathway organized by effective BIM implementation and internal stakeholder satisfaction with BIM outputs. This study indicates future research direction by providing both theoretical insights and practical consequences for construction project management, as well as concrete tactics to maximize project success in the BIM environment in the construction industry.
Keywords: Bim Benefits; Bim Implementation; Project Success; Top Management Support; Internal Stakeholder Satisfaction